2011
DOI: 10.1111/j.1537-2995.2011.03117.x
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of platelets, white blood cells, and hematopoietic progenitor cells during high‐yield plateletpheresis

Abstract: PLT recruitment during high-yield plateletpheresis facilitates the harvest of multiple PLT units in a single donation. The use of the ratio of recruited to yielded PLT may optimize the algorithm to predict PLT(post) . There was no recruitment of WBCs and HPCs during plateletpheresis. Therefore, the previously observed recruitment of HPCs during HPC apheresis seems to be related to other factors than the apheresis procedure itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…It is important to note however that apheresis collection and transfusion have inherent risks for donors and patients, as has recently being stressed . In this regard, platelet recruitment during high‐yield plateletpheresis has been documented and use of the ratio of recruited to yielded PLT has been proposed to optimize the algorithm to predict donor PLT count after apheresis . Donor's pre‐apheresis PLT count has been evaluated as a predictive factor of DP donations in a previous study .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note however that apheresis collection and transfusion have inherent risks for donors and patients, as has recently being stressed . In this regard, platelet recruitment during high‐yield plateletpheresis has been documented and use of the ratio of recruited to yielded PLT has been proposed to optimize the algorithm to predict donor PLT count after apheresis . Donor's pre‐apheresis PLT count has been evaluated as a predictive factor of DP donations in a previous study .…”
Section: Discussionmentioning
confidence: 99%
“…Heyns and colleagues have shown that two‐thirds of PLTs in normal persons remain in the circulation and the remainder one‐third is in an exchangeable pool in the spleen . Fontana et al went further to show that one‐third of PLTs collected in a single apheresis donation are recruited from the spleen . PLT post‐count predictions by cell separators that do not take into account this splenic release of PLTs will underestimate the effective PLT post‐count, which results in unnecessary PLT harvesting from plateletpheresis donors .…”
Section: Discussionmentioning
confidence: 99%
“…Fontana et al went further to show that one‐third of PLTs collected in a single apheresis donation are recruited from the spleen . PLT post‐count predictions by cell separators that do not take into account this splenic release of PLTs will underestimate the effective PLT post‐count, which results in unnecessary PLT harvesting from plateletpheresis donors . Current cell separator technologies including the Amicus Separator and Trima Accel (Caridian BCT, Lakewood, CO, USA) take into account this splenic release of PLTs and thus result in more efficient and accurate plateletpheresis collection yields than other cell separators .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations